The discovery of 5 millisecond pulsars in the high time resolution universe survey - Bates, S.; Bailes, M.; Bhat, Ramesh; Burgay, M.; Burke-Spolaor, S.; D'Amico, N.; Jameson, A.; Johnston, S.; Keith, M.; Kramer, M.; Levin, L.; Lyne, A.; et al. (2011)
We present the discovery of 5 millisecond pulsars found in the mid-Galactic latitude portion of the High Time Resolution Universe (HTRU) Survey. The pulsars have rotational periods from ~2.3 ms to ~7.5 ms, and all are in binary systems with orbital periods ranging from ~0.3 to ~150 d. In four of these systems, the most likely companion is a white dwarf, with minimum masses of ~0.2M ? . The other pulsar, J1731-1847, has a very low mass companion and exhibits eclipses, and is thus a member of the "black widow" class of pulsar binaries. These new discoveries occupy a short-period and high-dispersion measure (DM) region of parameter space, which we demonstrate is a direct consequence of the high time and frequency resolution of the HTRU survey. © 2011 American Institute of Physics.